Study and simulation of the radiation background of the ATLAS experiment at CERN using the Monte Carlo method - Lymperaiou, Maria (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών, 2017)
ATLAS is one of two general-purpose detectors at the Large Hadron Collider (LHC) at CERN. It investigates a wide range of physics, from the search for the Higgs boson to extra dimensions and particles that could make up dark matter. The ATLAS detector consists of a series of ever-larger concentric cylinders around the interaction point where the proton beams from the LHC collide. It can be divided into four major sections: Τhe Inner Detector, the innermost component, tracks the motion of charged particles as they move away from the interaction point. The tracks measured by recording particle/detector interactions at a multitude of discrete points, form the first step in identifying the unknown particles. The calorimeters measure the energy of both neutral and charged particles by interacting with them, resulting in creating cascades of secondary particles. The Muon Spectrometer, the outermost component of the detector, makes additional measurements of highly penetrating muons, which are capable of passing through the inner layers without interaction. Finally, the magnet systems bend charged particles in the Inner Detector and the Muon Spectrometer; their direction of motion and degree of curvature become indicative of their charge and momentum, respectively. The detector generates unmanageably large amounts of raw data: about 25 megabytes per event, multiplied by 40 million beam crossings per second in the center of the detector, producing a total of 1 petabyte of raw data per second. Thus, a trigger system is needed in order to select potentially interesting events for storage in real-time, so as to avoid being overwhelmed by background processes. The ATLAS trigger system uses simple information to identify the most interesting events to retain for detailed analysis. The data acquisition system receives and buffers the event data from the detector-specific readout electronics. Grid computing is being extensively used for event reconstruction, allowing the parallel use of computer networks throughout the world. A major problem at the ATLAS detector is the huge radiation background, coming from the collisions at the interaction point. This background causes several problems such as radiation damage to silicon detectors and readout electronics, ageing of the subdetectors, radiation deposits that disrupt electronic signals or destroy components, and background signals resulting in spurious and random triggers. For the limitation of these consequences, ATLAS uses almost 3000 tonnes of shielding in a multilayer design, taking advantage of the absorbing capacities of different materials. In the first chapter an introduction on the purposes and the physics studies of the LHC is presented. The second chapter describes the processes regarding the interactions of the various particles with matter, which may lead to the creation of new particles. An analysis of the LHC machine is carried out in the third chapter and a description of the ATLAS detector instrumentation and data processing follows in the fourth chapter. Chapter 5 presents the MCNP software, based on the Monte Carlo method, which is used for the design and the simulation of the various subdetectors of the experiment. The description of the radiation background and the shielding regions needed to curb the radiation effects in the subdetectors and the trigger system are analyzed in Chapter 6. The last chapter contains the methodology of the simulation and the results for the ATLAS subdetectors. Some additional simulations of simple geometries, as well as the MCNP code for the ATLAS detector are included in the appendices.